Tall cell carcinoma arising in a thyroglossal duct cyst: A case report. Issue 2 (June 2015) - Gordini, Luca; Podda, Francesco; Medas, Fabio; Lai, Maria Letizia; Longheu, Alessandro; Pisano, Giuseppe; Calò, Pietro Giorgio
Abstract: Introduction: Thyroglossal duct cyst carcinomas are extremely rare and their clinical presentation is similar to that of benign cysts. The diagnosis is based on physical examination, laboratory tests, and most importantly multiple imaging techniques (ultrasonography, computed tomography and magnetic resonance imaging), and fine needle aspiration cytology. Presentation of case: We report a very unusual case of a tall cell variant of papillary carcinoma arising in a thyroglossal duct cyst in association with a follicular variant of papillary microcarcinoma and a tall cell variant of papillary carcinoma arising from the thyroid gland. Discussion: Although rarely described in the medical literature, ectopic thyroid tissue present in the thyroglossal duct cyst could be involved in the development of a poorly differentiated carcinoma. The frequent observation of an associated primitive thyroid carcinoma makes surgical management of thyroid gland controversial. Conclusion: For the optimal management of this rare pathological condition, a comprehensive preoperative evaluation and meticulous intra-operative appraisal are fundamental. Highlights: TDCCs are uncommon but usually with a good prognosis. An association with thyroid primitive carcinoma is frequently observed. An extremely rare TDCC variant with a poor prognosis associated with two synchronous foci of thyroid carcinoma is reported. Surgical management of the thyroid gland within treatment plan is controversial. An accurate preoperative evaluation is mandatory for an optimal management.